Collective construction of bundle for immunobiological agents conservation best practices - Valéria Conceição de Oliveira; Patrícia Peres de Oliveira; Larissa Carvalho de Castro; Heloiza Maria Siqueira Rennó; Dayane Taís de Almeida Gonçalves; Ione Carvalho Pinto
ABSTRACT Objective: to construct collectively with nursing professionals bundle for best practices of cold chain maintenance of immunobiological agents conservation at the local level. Method: a qualitative research of convergent care type. Bundle construction was guided by the Evidence-Based Practice criterion. Data collection was carried out from October to December 2016, through five workshops, with the participation of 21 professionals from 7 vaccination rooms of a municipality of Minas Gerais State. The framework developed by Morse and Field was adopted for data analysis. Results: through bundle, care is taken regarding refrigeration equipment temperature monitoring, contingency plan performance, recyclable ice coil setting and chamber use as refrigeration equipment. Final considerations: the chosen interventions began to guide the practice and promote a care based on safety and quality.